Ts. Dr. Norazaliza develops more interesting, flexible, interactive and stress-free learning project - Hafizatulazlin, Abdul Aziz; Nur Hartini, Mohd Hatta (2021)
GAMBANG, 26 March 2021 - A lecturer at the Centre for Mathematical Sciences (PSM), Universiti Malaysia Pahang (UMP), Ts. Dr. Norazaliza Mohd Jamil, 37 and her teammates conducted a study entitled Interactive Cake-like MOOC Calculus to make the learning of Calculus more flexible.